The effect of surface texturing in the sliding surface on tribological characteristics of alloy steel under wet condition - H. S. Patil; D. C. Patel (Fracture and Structural Integrity)
Surface texturing plays an increasingly important role as it can directly influence the tribological behaviors of contact surfaces in many ways. In texturing, tribological performance depends upon the types of design texture used and methods of fabricating texture on the surface. In this research work, friction and wear behaviors of surface textured EN-31 alloy steel have been investigated under wet condition by using DUCOM linear reciprocating tribometer. The textured dimples are fabricated by micro-EDM and micro-drilling CNC machining processes. Initially un-textured surfaces of EN-31 alloy steel with EN-8 steel pin are experimented for friction and wear under ISO-68 and ISO-220 lubricant oil. Under the different normal load conditions, it has been observed that the ISO 68 oil gives better friction-wear characteristics with respect to ISO-220 oil. Then after textured surfaces were investigated by using optimized ISO-68 lubricant. Experimental results on micro-EDM provide better friction and wear properties with respect to micro-drilling CNC. Surface texturing may act as wear debris trapper, lubricant reservoirs, hydrodynamic lift, and retarding the lubricant molecules flow in a particular path where potential exists. In this work, it has observed that texturing by micro-EDM enhanced mixed lubrication and minimum friction in mixed lubrication leads to decrement of wear loss